Quality Characteristics of Clove Leaf Essential Oil Based on Leaf Pretreatment Using the Steam Distillation Method - Ida Ayu (Jurnal Online Pertanian Tropik, 2025)
Cloves are a plant that is often used as an ingredient in cooking or as an addition to cakes. The clove plant is not only used for its cloves, but its leaves can also produce great benefits. Some of the benefits of clove leaves include that they can be used for various types of treatment, including cough medicine, stomach ache medicine, and toothache medicine. The quite diverse chemical content in clove leaves provides quite open opportunities for use, one of which is being used as a raw material for producing essential oils. The aim of this research is to determine the suitability of the quality of the essential oil obtained in the form of yield, specific gravity, refractive index and solubility in 90% alcohol in accordance with the Indonesian National Standard (SNI) produced from clove leaves using the steam distillation method. The research method used in this research is an experimental method by conducting experiments in the laboratory. The treatments used were whole clove leaves (S1), clove leaves chopped at 50% (S2) and 25% (S3) of the total length of clove leaves, and crushed clove leaves (S4). The parameters of this research are yield, specific gravity, refractive index, and solubility in 90% alcohol. The results of the research showed that the best treatment was obtained from clove leaf samples chopped at 25% of the total leaf length which had the highest average yield and specific gravity, namely 2.88% and 1.061 g/ml. The refractive index value and the average solubility of clove leaf essential oil in each sample treatment met the Indonesian national standard (SNI 06-2387-2006).